2014
DOI: 10.1007/s00167-014-3367-9
|View full text |Cite
|
Sign up to set email alerts
|

No difference in anterior knee pain after medial unicompartmental knee arthroplasty in patients with or without patellofemoral osteoarthritis

Abstract: III.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
25
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(27 citation statements)
references
References 24 publications
2
25
0
Order By: Relevance
“…Kozinn and Scott proposed that UKA should not be offered to patients with PF joint arthritis for optimal results (31). This sparked a contentious debate on PF joint disease because other authors demonstrated only a weak correlation between PF degenerative changes and anterior knee pain (11,32).…”
Section: Discussionmentioning
confidence: 99%
“…Kozinn and Scott proposed that UKA should not be offered to patients with PF joint arthritis for optimal results (31). This sparked a contentious debate on PF joint disease because other authors demonstrated only a weak correlation between PF degenerative changes and anterior knee pain (11,32).…”
Section: Discussionmentioning
confidence: 99%
“…1 Also, similar results were shown that there was no significant difference in functional outcomes including anterior knee pain regardless of the presence or absence of OA in the patellofemoral joint. 1 However, some authors have concluded that the primary mode of failure of UKA was progressive PF OA which requires conversion to TKA. 4,5 Structural abnormalities in the subchondral bone are key factors in the pathogenesis of OA.…”
Section: Discussionmentioning
confidence: 99%
“…It is not clear why impingement and osteoarthritic changes appeared to have been mutually exclusive [16] [17]. Since impingement is associated with anterior placement of the femoral component, this complication may protect the opposite portion of the patella by reducing the contact pressures on that side [18] [19] [20].…”
Section: Discussionmentioning
confidence: 99%